The Activities of Antifertility Ethanol Extract Guava Leaves (Psidium Guajava L.) based on The Analysis Of Cement and Display of Immunohistochemistry Cyclooxygenase-2 In Testis Of Mice (Mus Musculus L.) - RICA VERA BR TARIGAN; M. PANDAPOTAN NASUTION; SRY SURYANI WIDJAJA (Fakultas Farmasi Universitas Pancasila, 2016)
Population growth increase, without support from good economic conditions, requirer population control. One of the program to control population growth is family planning program (KB). The participation of men in family planning programs is very important. Male contraception can utilize natural materials derived from plants. One of the herb is guava leaves (Psidium guajava L.) which contains many active substances that can inhibit the process of spermatogenesis. The purpose of this study was to determine the effect of ethanol extract guava leaves to the quality (concentration, viability, morphology, and motility) of spermatozoa and the expression of Cyclooxygenase-2 (COX-2) in the testes of mice (Mus musculus L.). The research used experimental design with completely randomized sampling method. Four treatment groups, namely P0 using aquadest as a control 0,5 mL, P1 using 15 mg/25g body weight extract orally, P2 using 20 mg/25g body weight extract orally, and P3 using 25 mg/25g body weight extract orally. Data were analyzed using One Way ANOVA followed by Bonferroni Post Hoc test 5%. The results showed that ethanol extract guava leaves with a dose of 15mg/25g body weight had significantly decreased sperm quality and increased expression of COX-2 in the testes of mice. This research indicates that guava leaves have a potential to be used as a herbal contraceptive.